"Sticks and Stones May Break My Bones, but Words Will Never Hurt Me": Verbal Sexual Harassment Among Middle School Students. (September 2020) - Rolfe, Shawn M.; Schroeder, Ryan D.
Research has recently found that sexual harassment occurs throughout our education system. Although the focus of these studies has been on both verbal and physical sexual harassment, the literature is scant when examining just verbal sexual harassment. Using self-report data from 30 New York City middle schools, the current study adds to the literature by examining the prevalence of verbal sexual harassment victimization and perpetration through the lens of gender and dating experiences. The study highlights that boys are verbally sexually harassed more than girls and students with dating experience are more likely to be victims or perpetrators of verbal sexual harassment. Additional findings, limitations, and policy implications are discussed.